An in vitro assay for toxicity testing of Clostridium perfringens type C β-toxin - Hoonakker, Marieke; Zariri, Afshin; de Brouwer, Lisette; David, Dionne; Borgman, Anouska; Sloots, Arjen (Frontiers in Immunology, 2024)
Introduction Veterinary vaccines against Clostridium perfringens type C need to be tested for absence of toxicity, as mandated by pharmacopoeias worldwide. This toxicity testing is required at multiple manufacturing steps and relies on outdated mouse tests that involve severe animal suffering. Clostridium perfringens type C produces several toxins of which the β-toxin is the primary component responsible for causing disease. Here, we describe the successful development of a new cell-based in vitro assay that can address the specific toxicity of the β-toxin. Methods Development of the cell-based assay followed the principle of in vitro testing developed for Cl. septicum vaccines, which is based on Vero cells. We screened four cell lines and selected the THP-1 cell line, which was shown to be the most specific and sensitive for β-toxin activity, in combination with a commercially available method to determine cell viability (MTS assay) as a readout. Results The current animal test is estimated to detect 100 – 1000-fold dilutions of the Cl. perfringens type C non-inactivated antigen. When tested with an active Cl. perfringens type C antigen preparation, derived from a commercial vaccine manufacturing process, our THP-1 cell-based assay was able to detect toxin activity from undiluted to over 10000-fold dilution, showing a linear range between approximately 1000- and 10000-fold dilutions. Assay specificity for the β-toxin was confirmed with neutralizing antibodies and lack of reaction to Cl. perfringens culture medium. In addition, assay parameters demonstrated good repeatability. Conclusions Here, we have shown proof of concept for a THP-1 cell-based assay for toxicity testing of veterinary Cl. perfringens type C vaccines that is suitable for all vaccine production steps. This result represents a significant step towards the replacement of animal-based toxicity testing of this veterinary clostridial antigen. As a next step, assessment of the assay’s sensitivity and repeatability and validation of the method will have to be performed in a commercial manufacturing context in order to formally implement the assay in vaccine quality control.